In situ observation of δ phase suppression by lattice strain in all-inorganic perovskite solar cells. (July 2020) - Hui, Wei; Xu, Ying; Xia, Fei; Lu, Hui; Li, Bixin; Chao, Lingfeng; Niu, Tingting; Du, Bin; Du, Haiyan; Ran, Xueqin; Yang, Yingguo; Xia, Yingdong; et al.
Abstract: The phase control and ordered crystal growth play a crucial role in the efficiency and stability of all-inorganic perovskite solar cells (PSCs). However, the innate dynamics of crystal growth driving the stable phase and high performance are unknown. Here, we for the first time unraveled that the degree of lattice strain is responsible for the suppression of the δ phase growth by in situ Grazing-Incidence Wide-Angle X-ray Scattering (GIWAXS) technique. We shadow the internal crystal structural changes in real time and successfully decoupled crystal growth dynamics under different substrate temperatures. The symmetrical crystal lattice and vertical substrate growth were finally achieved. This finding provides insights on the inorganic perovskite crystal growth and has significant benefit for high performing all-inorganic PSCs. Graphical abstract: We unraveled that the degree of lattice strain is responsible for the suppression of the δ phase growth in all-inorganic CsPbI2 Br perovskite solar cells. Image 1 Highlights: Revealing the relationship between strain and phase transitions in CsPbI2 Br perovskite films by in-situ GIWAXS technique. Controlling the strain during the growth of the perovskite film. Inhibiting the appearance of the non-perovskite phase completely, and obtained a perovskite film with a vertical plane growth.